2014
DOI: 10.5194/angeo-32-1223-2014
|View full text |Cite
|
Sign up to set email alerts
|

E layer dominated ionosphere observed by EISCAT/ESR radars during solar minimum

Abstract: Abstract. According to the study by Mayer and Jakowski (2009), periods of E layer dominated ionosphere (ELDI) are defined as being characterized by vertical electron density profiles having a maximum density at E layer altitudes. In this paper, characteristics of ELDI intervals have been investigated, focusing on their temporal variations, using field-aligned measurements from the EIS-CAT and ESR radars during the interval 2009-2011. ELDI events were identified using simple but reasonable criteria, in which a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
7
7
0
Order By: Relevance
“…The plots show a maximum of %ELDI in local winter and a minimum in local summer. This result fits the findings of Cai et al [6], who have found out from the analysis of incoherent scatter radar data that more ELDI events emerged in winter and early spring for both the EISCAT and the ESR site.…”
Section: Diurnal Variationsupporting
confidence: 92%
See 4 more Smart Citations
“…The plots show a maximum of %ELDI in local winter and a minimum in local summer. This result fits the findings of Cai et al [6], who have found out from the analysis of incoherent scatter radar data that more ELDI events emerged in winter and early spring for both the EISCAT and the ESR site.…”
Section: Diurnal Variationsupporting
confidence: 92%
“…The plots reveal that in all cases %ELDI reaches its maximum around local night and its minimum around local noon. This result confirms the findings of Mayer and Jakowski [4], who have also observed an increase in ELDI occurrence during nighttime for the entire northern high latitude region, while Cai et al [6] have found a similar trend for the EISCAT site. Especially for the COSMIC mission, due to the large amount of profiles, our plots are smoothed out and show a clearly sinusoidal trend over the course of a day.…”
Section: Diurnal Variationsupporting
confidence: 91%
See 3 more Smart Citations